Parameters controlling stiffness and strength of artificially cemented soils - N. C. Consoli (2012)
The treatment of soils with cement is an attractive technique when a project requires improvement of the local soil for the construction of subgrades for rail tracks, for roads, as a support layer for shallow foundations, and to prevent sand liquefaction. This paper advances understanding of the key parameters for the control of strength and stiffness of cemented soils by testing two soils with different gradings and quantifying the influence of porosity/cement ratio on both initial shear modulus (G(0)) and unconfined compressive strength (q(u)). It is shown that the porosity/cement ratio is an appropriate parameter to assess both the initial stiffness and the unconfined compressive strength of the soil-cement mixtures studied. Each soil matrix has a unique relationship for G(0)/q(u) against adjusted porosity/cement ratio, linking initial stiffness and strength.